Thực trạng hành vi lệch chuẩn của học sinh các trường Trung học cơ sở và Trung học phổ thông trên địa bàn thành phố Hà Nội - Lê, Thị Khánh Ly (Tạp chí Thiết bị Giáo dục, 2023)
Deviant behavior is increasing and becoming a concern of the whole society. This study investigates the status of standard deviation behavior of 860 students from 6 middle schools and high schools in Hanoi city. Research has shown that: Deviant behaviors take place in middle and high school students in Hanoi city, but at a low level, deviant behavior occurs in both boys and girls. However, this study was only carried out in Hanoi city. These are also suggestions for further studies in different locations.